Anionic flow polymerizations toward functional polyphosphoesters in microreactors: Polymerization and UV-modification - Baeten, Evelien; Vanslambrouck, Stephanie; Jérôme, Christine; Lecomte, Philippe; Junkers, Tanja (European polymer journal, 2016)
[Display omitted] •Poly(phosphoester)s, PPEs have been successfully polymerized in microstructured flow reactors.•By using flow chemistry, reaction rates are increased and side reactions reduced.•Alkene-functional PPEs have been obtained that allow for UV-induced modification of the backbone, also in flow.•The thermally activated polymerization could be directly coupled to the UV modification in a reactor cascade. The polymerization of cyclic phosphates to poly(phosphoester)s, PPEs, is optimized for chip-based microreactors under continuous flow conditions. The anionic ring-opening polymerization of 2-isobutyoxy-2-oxo-1,3,2-dioxaphospholane (iBP) via the use of two organocatalytic systems allowed to polymerize to nearly quantitative monomer conversion within 10 or 3min, respectively at a reaction temperature of 40°C. Further, the optimized polymerization protocol was applied to 2-butenoxy-2-oxo-1,3,2-dioxaphospholane (BP) which yields a polymer that carries an alkene functionality per monomer repeating unit. This material can be postmodified in an UV-induced radical thiol–ene reaction, which was also shown to proceed with very high efficiency under UV-flow conditions. Eventually, both reactions were coupled in a two-stage reactor setup, showing that the thermally-activated polymerization can be coupled with high efficiency to the UV-activated post-polymerization modification reaction. The introduced reactor setup can in the future be used to produce and screen a broad variety of functional PPE materials with various functionalities and physical properties.